1993
DOI: 10.1016/0304-3940(93)90575-6
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase-immunoreactive neurons in human and porcine respiratory tract

Abstract: The presence of nitric oxide synthase (NO-synthase), the enzyme responsible for the production of nitric oxide (NO) from L-arginine, is shown immunocytochemically in the intrinsic neurons of the human and porcine respiratory tract. NO-synthase immunoreactivity is demonstrated in a subpopulation of neurons of the microganglia present in the wall of the extra- and intrapulmonary bronchi as well as in the hilar region of the lung in relation to blood vessels. The immunostaining was also found in some nerve fibers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…Our demonstration of an age and airway generation-related transition in functional control over smooth muscle tone is supported for immunohistochemical studies suggesting NOSimmunoreactive (NOS-IR) nerves decrease with age in both pig and man (Diaz de Rada et al, 1993). Our ®ndings of a predominantly central airway distribution of nitrergic relaxation in the adult is consistent with studies suggesting that NOS-IR nerves are most dense in the central airways of guinea-pig, horse, rat, pig and human respiratory tracts, but absent in the bronchioli (Fischer et al, 1993;Kobzik et al, 1993;Diaz de Rada et al, 1993;Yu et al, 1994;Ward et al, 1995a). In the cat there is evidence for actions of multiple inhibitory neurotransmitters at dierent levels of the tracheobronchial tree, with nitrergic mechanisms prominent in the central airway with a non-nitrergic mechanism prominent in bronchi, which is consistent with our ®ndings (Takahashi et al, 1995;Kondo et al, 1995).…”
Section: Discussionsupporting
confidence: 67%
“…Our demonstration of an age and airway generation-related transition in functional control over smooth muscle tone is supported for immunohistochemical studies suggesting NOSimmunoreactive (NOS-IR) nerves decrease with age in both pig and man (Diaz de Rada et al, 1993). Our ®ndings of a predominantly central airway distribution of nitrergic relaxation in the adult is consistent with studies suggesting that NOS-IR nerves are most dense in the central airways of guinea-pig, horse, rat, pig and human respiratory tracts, but absent in the bronchioli (Fischer et al, 1993;Kobzik et al, 1993;Diaz de Rada et al, 1993;Yu et al, 1994;Ward et al, 1995a). In the cat there is evidence for actions of multiple inhibitory neurotransmitters at dierent levels of the tracheobronchial tree, with nitrergic mechanisms prominent in the central airway with a non-nitrergic mechanism prominent in bronchi, which is consistent with our ®ndings (Takahashi et al, 1995;Kondo et al, 1995).…”
Section: Discussionsupporting
confidence: 67%
“…De Rada et al [75] revealed the presence of NOS-immunoreactive neurons in the human and porcine respiratory tract and blood vessels. From studies on NOS-containing nerve fibers in the human airway muscle and blood vessels, Fischer and Hoffmann [76] suggested the functional differences of the neural relaxant responses were mediated by nitric oxide at different levels of the airway tree.…”
Section: Neurogenic Nitric Oxide In Pulmonary Hypertensionmentioning
confidence: 98%
“…11,12 Airway neurons that are immunoreactive for NOS are less prominent in peripheral than in central human airways. 13,14 NO also seems essential for ciliary motility, 15 and its antimicrobial properties have been shown to be important in host defense against various pathogens. 16,17 However, excess NO formation as in septic shock causes inflammation, oxidative tissue damage, and favors plasma leakage into perivascular spaces and the airway lumen 18 through reactive intermediates such as peroxynitrite anion (ONOO − ) or peroxynitrous acid (OONOH), both rapidly formed by the interaction of NO and superoxide anion (O 2 − ).…”
Section: Introductionmentioning
confidence: 99%